DIVERGENCE REGARDING ESG. A BIBLIOMETRIC ANALYSIS - VASIU Diana Elena (Management of Sustainable Development, 2024)
ESG criteria serve as a cornerstone for sustainable business practices, but the growing emphasis on sustainability has led to a surge in ESG rating providers, introducing significant challenges. ESG ratings are inherently complex and often differ across agencies, due to a lack of standardized parameters, risks of green-washing, and the perceived trade-off between profitability and sustainability. Inconsistent methodologies and fragmented regulatory frameworks hinder meaningful comparisons, resulting in limited confidence among investors and companies regarding the reliability of these ratings. Nevertheless, ESG advocates view these ratings as drivers of long-term financial and societal benefits. Consequently, researchers are increasingly focused on understanding the extent of ESG rating divergence, identifying its underlying causes, evaluating its impact on company performance, and exploring strategies to mitigate the negative effects of these inconsistencies. This paper provides an overview of the topic of “ESG ratings divergence,” a subject that has seen exponential growth in the past three years. Using a bibliometric approach, it examines the academic literature published and indexed in the Scopus database with the help of VOSviewer.